Adaptation genre of Ukrainian folk songs in the interpretation of K. Gorski: aspects of texture stylistics (International Journal of Scientific Research and Management (IJSRM), 2021)
The article examines the adaptation principles of Ukrainian folklore material used by an outstanding representative of the Polish-Ukrainian branch of the musical culture of Kharkov at the turn of the XIX – XX centuries. For the analysis, a collection-cycle was selected, compiled by the author himself on the basis of adaptations of the songs used in the operetta “Oi Bozhe shcho ta liubov zmozhe!” for the libretto by A. Zbukireva, staged by M. Kropyvnytsky, one of the founders of the Ukrainian national theater. Several groups of adaptations are outlined and classified, representing the portraits of the characters of the operetta, as well as the stage situations. Generalizing characteristics of the texture-stylistic approaches used by K. Gorski in the piano parts, prefixed to each of the 20 songs, are given. It is noted that K. Gorski not only demonstrates professional mastery of adaptation techniques approved in classical music, but also translates features of Ukrainian folk polyphony into texture and harmony, which gives his adaptation an individualized charm.